2017
DOI: 10.5603/arm.2017.0035
|View full text |Cite
|
Sign up to set email alerts
|

Metastasising Leiomyoma of the Uterus with Pulmonary Involvement—Case Report

Abstract: Benign metastasising leiomyoma (BML) is characterised by extrauterine smooth muscle tumours in women after surgical treatment for uterine leiomyoma. Usually manifested as solitary or multiple focal lesions in various organs, it imposes a scrutinous diagnostic work-up to exclude a malignant disease and requires confirmation in microscopic examination of the extrauterine focus. The authors present a case of a 56-year-old woman with BML manifesting as bilateral multiple pulmonary nodules, with a tentative diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…In all cases, the patients underwent a signi cant number of tests before a decision to use invasive diagnostics and surgery was made. This is the typical course of events for "yet to be diagnosed" BPML patients: only unspeci c clinical features are revealed by the examinations of rst resort [22].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In all cases, the patients underwent a signi cant number of tests before a decision to use invasive diagnostics and surgery was made. This is the typical course of events for "yet to be diagnosed" BPML patients: only unspeci c clinical features are revealed by the examinations of rst resort [22].…”
Section: Discussionmentioning
confidence: 97%
“…In accord with other authors, in the two patients the neoplastic changes were found years (12 and 17 years, respectively) after the operation for uterine leiomyoma, and their presence failed to be noted in any of the routine chest X-rays over this time. This makes the question of whether the myometrium is truly the primary locus of the BPML even more valid [22]. In the third case lung lesions have been diagnosed before the hysterectomy.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The diagnosis of BML remains challenging, as patients are often asymptomatic, and the mean interval between initial surgery and diagnosis of BML is approximately nine years. However, cases of BML have been identified as early as the time of initial surgery and as late as 31 years postoperatively [ 20 , 21 , 22 ]. The patients described in this paper had notably different histories.…”
Section: Discussionmentioning
confidence: 99%